Traditional Car Repair Apprenticeship and Social Change in the Brotojoyo Community, Semarang - Amin Yusuf; Mintarsih Arbarini; Decky Avrilianda (MASI Mandiri Edukasi, 2026)
While formal vocational training is widely explored, the learning mechanisms and Socio-economic impacts of traditional apprenticeships in urban informal vocational communities remain underexplored. This qualitative case study analyses traditional apprenticeship learning patterns and their Socio-economic impacts within a car repair community in Brotojoyo, Semarang. Data were collected from nine participants three experts, three apprentices, and three community leaders via in-depth interviews, observation, and documentation, and then analyzed using the Miles and Huberman interactive model. Findings reveal that the apprenticeship progresses gradually from observation and guided practice to full independence through specific episodes, including negotiation, unloading, workmanship, installation, and finishing. Ultimately, these structured yet informal learning phases significantly enhance apprentices' technical skills and economic welfare, while fostering social solidarity grounded in local wisdom values such as discipline, trust, mutual help, patience, and work responsibility. Theoretically, this study integrates traditional apprenticeship patterns with contextual learning theory. In practice, it offers an alternative, localized model for community empowerment to reduce unemployment and strengthen social capital.